THE POSSIBILITY OF ETHICAL BUSINESS - Mabaquiao, Napoleon (Journal of Dharma, 2020)
As the business activity is an integral part of our social life, building an ethical society must include, among others, ensuring the ethical conduct of this activity. The concept of ethical business, however, has always been controversial especially in light of the alleged incompatibility of the profit motive with the motive of benevolence. Accordingly, it is thought that the profit motive is essentially selfish which thereby contradicts the selfless motive of benevolence. A standard strategy for reconciling these two motives takes the profit motive as a means to perform benevolent acts, which, however, only separates the business act from the ethical one. This essay advances an alternative strategy in which said motives occur simultaneously as motives for performing the same act. After demonstrating its possibility through a case involving General Motors, the essay shows how this strategy can be ethically justified using the Kantian moral principle of respect for persons.